The association between anserine bursa pain and fall susceptibility: a prospective analysis of the osteoarthritis initiative - Wang, Fugui; Xiao, Jianhua; Song, Zhi; Zhang, Chao; Zhu, Zhengyuan (Frontiers in Aging, 2025)
BackgroundAnserine bursa pain (ABP) is hypothesized to correlate with early-stage knee osteoarthritis (KOA). This research seeks to investigate the link between ABP and the incidence of falls in patients diagnosed with KOA or those at heightened risk of developing this condition.MethodThe study utilized 2-year follow-up data derived from the Osteoarthritis Initiative cohort, a comprehensive multicenter observational investigation. Assessment of ABP was conducted through a tenderness/pain evaluation of the anserine bursa, while fall occurrences were self-reported by participants. Binary logistic regression was conducted, adjusting for confounding variables, and results were expressed as ORs along with their 95% CIs.ResultsData from 3,654 participants were analyzed, with 33.3% reporting ABP. Throughout the follow-up duration, 1,668 participants recorded instances of falls, 1,986 reported no falls, and 244 experienced recurrent falls annually. The primary outcome focused on incident falls, revealing a significant association between ABP and the odds of incident falls over the 2-year follow-up (odds ratio (OR) = 1.188, 95% Confidence interval (CI): 1.021–1.383, P = 0.026). When recurrent falls were included as an additional outcome, ABP was found to markedly predict the odds of these incidents over the 2-year follow-up (OR = 1.422, 95% CI: 1.065–1.898, P = 0.017). Sensitivity analyses confirmed the robustness of these findings among female participants and those without a prior history of falls.ConclusionWithin individuals diagnosed with KOA or those at substantial risk for KOA, a significant association exists between ABP and increased odds of falling over the 2-year follow-up.